2010
DOI: 10.4103/0973-6247.67022
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of B19 IgG ELISA to study the seroepidemiology of parvovirus B19 in North Indian voluntary blood donors

Abstract: Backgound and Objectives:Parvovirus B19 (B19) being a non-enveloped DNA virus is hence thermo-stable to the current methods of viral inactivation. Therefore transfusion of blood or its component from a viremic donor to non-immune recipients may result in transfusion-transmitted B19 infection with occasional sinister complications. The serologically naïve blood donor population in our country has not been studied. Hence a study was designed to find the sero-status of B19 virus in normal voluntary blood donor po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
6
13
0
Order By: Relevance
“…Pregnant women that have been transfused with blood in the last five years demonstrated a significantly higher rate of IgM antibodies. This finding agrees with reports that linked B19 infection with blood transfusion (Parsyan & Candotti 2007, Kishore et al 2010 and raises an important transfusion policy question in Nigeria. Given the nature of the complications of B19 infection during pregnancy, we recommend, as a matter of transfusion policy, routine screening for B19 IgM antibodies in all blood donors, especially those donating to women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Pregnant women that have been transfused with blood in the last five years demonstrated a significantly higher rate of IgM antibodies. This finding agrees with reports that linked B19 infection with blood transfusion (Parsyan & Candotti 2007, Kishore et al 2010 and raises an important transfusion policy question in Nigeria. Given the nature of the complications of B19 infection during pregnancy, we recommend, as a matter of transfusion policy, routine screening for B19 IgM antibodies in all blood donors, especially those donating to women.…”
Section: Discussionsupporting
confidence: 91%
“…The low prevalence of 27.5% from our study indicates that a lower proportion of immune individuals participated in our study population. However, consistent with our findings, Kishore et al (2010) reported a low seroprevalence of 39.9% in a population of Indian blood donors, which led him to conclude that a large proportion of north Indians are susceptible to infection with B19. The 21.8% prevalence reported by Keikha et al (2006) in a population of Iranian pregnant women also agrees with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, positivity of IgG antibodies in women was slightly significantly higher than in men (73.4% vs. 70.8%, respectively). In a study conducted in India, Kishore et al (15) reported that seroprevalence of B19 in adult blood donors increased with age and the overall seroprevalence of the antibody was 39.9%, higher in males than in females (44% vs. 27%, respectively). Su et al (16), in Taiwan, reported that overall seroprevalence of B19 IgG in healthy volunteers was 23.1%, that the positive rate of the antibody increased slightly with age, and that the antibody rate was slightly higher in men than in women (27.8% vs. 18.8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Serum was tested for human parvovirus B19 by ELISA and polymerase chain reaction (PCR) as described previously [4,5] and real-time PCR (Shanghai, China). Anti-B19 IgM, IgG were positive but no B19 DNA was detected.…”
mentioning
confidence: 99%